Frontispiece: Reversible pH‐Responsive Coacervate Formation in Lipid Vesicles Activates Dormant Enzymatic Reactions. Issue 15 (1st April 2020) - Love, Celina; Steinkühler, Jan; Gonzales, David T.; Yandrapalli, Naresh; Robinson, Tom; Dimova, Rumiana; Tang, T.‐Y. Dora
Abstract : Systems Chemistry In their Communication on page 5950, T.‐Y. D. Tang et al. report the use of the pH responsiveness of a polycation to drive liquid–liquid phase separation to form coacervate droplets within lipid vesicles to control enzyme activity.